The financial Impacts of (COVID-19) on financial reporting quality Airlines Companies: British Airlines - Hamawandy, Nawzad Majeed; Ali, Ranjdar; AL .Bewani, Hemn Adl Wali; Jamil, Diyar bdulmajeed; Rahman, Shorsh Khaild; Othman, Baban Jabbar (The journal of contemporary issues in business and government, 2021)
At the beginning of 2020, China declared a state of emergency due to the spread of the new Corona virus in Wuhan, which is one of its largest major industrial cities, and the new disease was soon detected as an epidemic in China, and on March 11, the World Health Organization classified COVID-19. However, it is a pandemic due to the large increase in the number of cases infected with this disease in all countries of the world. Based on the precautionary measures taken by all countries to limit the spread of the virus, and considering the aviation sector is the fastest means of transmission around the world, flights of this sector have been suspended between all countries in order to contain the epidemic. The COVID-19 outbreak across the world has imposed a series of social distancing restrictions for motivating the impact of the pandemic (Coftas et al. 2020). Airlines are also severely affected by the pandemic (Sparke & Anguelov, 2020). The proposed research is based on analysing restrictions caused by the COVID-19 on the efficacy of airlines with respect to new social distancing norms (Seo and Itoh, 2020). For this purpose, the focus is on British Airlines, which is one of the largest airlines in the world being greatly hit by the ongoing pandemic. The COVID-19 outbreak across the world has imposed a series of social distancing restrictions for motivating the impact of the pandemic (Coftas et al. 2020).Airlines are also severely affected by the pandemic (Engström et al. 2020). The proposed research is based on analysing restrictions caused by the COVID-19 on the efficacy of airlines with respect to new social distancing norms. For this purpose, the focus is on British Airlines, which is one of the largest airlines in the world being greatly hit by the ongoing pandemic.